Hypoxia‐Driven Neurovascular Impairment Underlies Structural‐Functional Dissociation in Diabetic Sudomotor Dysfunction - Xu Guo; Chao Zhang; Yuzhen Wang; Zhao Li; Yaxin Tan; Dongzhen Zhu; Wei Song; Yi Kong; Jinpeng Du; Yuyan Huang; Liting Liang; Jianjun Li; et al. (MedComm)
ABSTRACT Sudomotor dysfunction in diabetic patients increases the risk of fissures, infections, and diabetic foot ulcers (DFUs), thereby reducing the quality of life. Despite its clinical importance, the mechanisms underlying this dysfunction remain inadequately elucidated. This study addresses this gap by demonstrating that despite structural integrity, sweat glands (SGs) in diabetic individuals with DFUs, and a murine model of diabetic neuropathy (DN), exhibit functional impairments, as confirmed by histological and functional assays. Integrated transcriptome and proteome analysis revealed significant upregulation of the SG microenvironment in response to hypoxia, highlighting potential underlying pathways involved. In addition, histological staining and tissue clearing techniques provided evidence of impaired neurovascular networks adjacent to SGs. Single‐cell RNA sequencing unveiled intricate intercellular communication networks among endothelial cells (ECs), neural cells (NCs), and sweat gland cells (SGCs), emphasizing intricate cellular interactions within the SG microenvironment. Furthermore, an in vitro SGC–NC interaction model (SNIM) was employed to validate the supportive role of NCs in regulating SGC functions, highlighting the neurovascular‐SG axis in diabetic pathophysiology. These findings confirm the hypoxia‐driven upregulation of the SG microenvironment and underscore the critical role of the neurovascular‐SG axis in diabetic pathophysiology, providing insights into potential therapeutic targets for managing diabetic complications and improving patient outcomes.